Entwicklung einer Auswertemethode für bruchmechanische Versuche an kleinen Proben auf der Basis eines Kohäsivzonenmodells - Mahler, Michael (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2016)
In this work, the fracture toughness is predicted by means of a method based on tests using sub-size specimens. For this purpose, the fracture process including crack growth is described using FEM and cohesive zone model. The tests on sub-size specimens are used for parameter identification. With this set of parameters a standard-size specimen can be simulated. The predicted fracture toughness based on this standard-size specimen meets the size-requirements of the applicable standard.